Temporal association of rotavirus vaccination and genotype circulation in South Africa: Observations from 2002 to 2014. Issue 47 (12th November 2018) - Page, N.A.; Seheri, L.M.; Groome, M.J.; Moyes, J.; Walaza, S.; Mphahlele, J.; Kahn, K.; Kapongo, C.N.; Zar, H.J.; Tempia, S.; Cohen, C.; Madhi, S.A.
Highlights: Rotavirus vaccination was associated with temporal changes in circulating genotypes. The proportion of genotype G1 strains declined after vaccine introduction. The proportion of non-G1P[8] strains increased after vaccine introduction. Genotype changes did not affect the reduction in rotavirus disease in South Africa. Abstract: Background: Rotavirus vaccination has reduced diarrhoeal morbidity and mortality globally. The monovalent rotavirus vaccine was introduced into the public immunization program in South Africa (SA) in 2009 and led to approximately 50% reduction in rotavirus hospitalization in young children. The aim of this study was to investigate the rotavirus genotype distribution in SA before and after vaccine introduction. Materials and methods: In addition to pre-vaccine era surveillance conducted from 2002 to 2008 at Dr George Mukhari Hospital (DGM), rotavirus surveillance among children <5 years hospitalized for acute diarrhoea was established at seven sentinel sites in SA from April 2009 to December 2014. Stool specimens were screened by enzyme immunoassay and rotavirus positive specimens genotyped using standardised methods. Results: At DGM, there was a significant decrease in G1 strains from pre-vaccine introduction (34%; 479/1418; 2002–2009) compared to post-vaccine introduction (22%; 37/170; 2010–2014; p for trend <.001). Similarly, there was a significant increase in non-G1P[8] strains at this site (p for trend <.001). In expanded sentinel surveillance, when adjusted for age and site, the odds of rotavirus detection in hospitalized children with diarrhoea declined significantly from 2009 (46%; 423/917) to 2014 (22%; 205/939; p < .001). The odds of G1 detection declined significantly from 2009 (53%; 224/421) to 2010–2011 (26%; 183/703; aOR = 0.5; p < .001) and 2012–2014 (9%; 80/905; aOR = 0.1; p < .001). Non-G1P[8] strains showed a significant increase from 2009 (33%; 139/421) to 2012–2014 (52%; 473/905; aOR = 2.5; p < .001). Conclusions: Rotavirus vaccination of children was associated with temporal changes in circulating genotypes. Despite these temporal changes in circulating genotypes, the overall reduction in rotavirus disease in South Africa remains significant.